IMPLEMENTASI PERATURAN PEMERINTAH (PP) NO. 46 TAHUN 2013 DIBANDINGKAN DENGAN PPH PASAL 31 EUU NO. 36 TAHUN 2008 DALAM PERHITUNGAN PAJAK PENGHASILAN TERHUTANG PADA CV. SINAR GEMILANG MAKASSAR - Haeruddin Haeruddin (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2016)
Implementation of Government Regulation (PP) No. 46 of 2013 as compared to Article 31e Income Tax Act 36 of 2008 in Calculation of Income Tax Payable on CV.Sinar Gemilang Makassar. With quantitative analysis Calculation of Income Tax Payable by using PP No. 46 of 2013 (Final Tax) to the taxpayer less than the Calculation of Tax Article 31 (e) of Law No. 36 Year 2008, while the qualitative analysis, the implementation of PP 46 in 2013 facilitate calculation, paying and reporting Taxpayers of Income Tax Payable (WP).